Food safety knowledge, attitude and practice awareness among food consumer at The Chicken Rice Shop, Tesco Mutiara Damansara / Amirah Aisyah Amir and Nur Haziyah Mohd Rosidi - Amir, Amirah Aisyah; Mohd Rosidi, Nur Haziyah (2018)
Consumers and food operators are an important part of preventing foodbome illness. The purpose of this study is to investigate the safety knowledge, attitude and awareness of food practices among food users at The Chicken Rice Shop, Tesco Mutiara Damansara. The result indicates beta coefficient, the most variable awareness among consumer is practice with knowledge 0.062, attitude 0.109 and last is practice 0.174. This result show that, consumers at The Chicken Rice Shop, Tesco Mutiara Damansara are more know about practice compare knowledge and attitude.